(untitled) (Research, Society and Development, 2020)
Introduction: The idiopathic bone cavity is a lesion with a cystic radiographic appearance that can affect any bone. Especially in maxillary bones it represents about 1% of cystic lesions, a fact that can be underestimated since biopsy and clinical diagnosis can be dispensed with given the course and characteristics of the lesion. Methodology: This systematic review of the literature was carried out by searching the PubMed, SciELO, LILACS and OpenGrey databases. Results: Among the 21 studies included, most were from a retrospective cohort, with a total sample of 401 patients, with a minimum age of 7 years and a maximum age of 75 years. The lesions were located according to the following number of patients: posterior mandible region (268), anterior mandible region (104) and maxilla (30). In 40 patients there was bone expansion. Regarding radiographic characteristics, 369 patients presented lesions with unilateral distribution and 29 with bilateral location, while the unilocular pattern was present in 97 and the multilocular pattern in 23 patients. Conclusion: the idiopathic bone cavity is predominantly found during the first two decades of life in patients of both sexes, has a greater incidence in the posterior region of the mandible, is generally asymptomatic, radiographically presenting itself incisively as a radiolucent lesion. unilocular with air, blood or serous liquid inside, with surgical exploration and curettage as the treatment of choice and a low recurrence rate.